THE ROLE OF INFORMATION TECHNOLOGIES IN REGULATING FUEL CONSUMPTION IN MOTOR TRANSPORT (British Journal of Global Ecology and Sustainable Development, 2024)
The increasing demand for sustainable transportation solutions has necessitated the development and implementation of advanced information technologies (IT) to regulate fuel consumption in motor transport. This paper explores the pivotal role that IT plays in enhancing fuel efficiency, reducing emissions, and promoting economic savings within the transport sector. Key technologies such as telematics, GPS tracking, big data analytics, and intelligent transportation systems (ITS) are examined for their contributions to monitoring and optimizing fuel use. The integration of these technologies enables real-time data collection and analysis, providing actionable insights for fleet management and individual vehicle operation. Case studies from various regions and industries illustrate the practical benefits and challenges associated with adopting these technologies. The findings suggest that while IT-driven solutions significantly improve fuel management, successful implementation requires overcoming barriers related to cost, technological complexity, and user acceptance. Ultimately, this research highlights the transformative potential of information technologies in achieving more sustainable and efficient motor transport systems.